Optimizing Sleep in Older Adults: Where Does High-Intensity Interval Training Fit? - Bullock, Alexis; Kovacevic, Ana; Kuhn, Tara; Heisz, Jennifer J. (Frontiers in Psychology, 2020)
The present community-based study evaluated the effect of three different exercise interventions on sleep quality. Older adults were enrolled in one of three exercise intervention groups: high-intensity interval training (HIIT; n=20), moderate-intensity continuous training (MICT; n=19) or stretching (STRETCH; n=22). Prior to and following the intervention, sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). The PSQI was used to classify participants as poor (global PSQI score 5) or good (global PSQI score >5) sleepers and the effect of the intervention was examined on poor sleepers only. 70% of our sample were classified as poor sleepers. Poor sleepers were significantly impaired across all PSQI components, except for the use of sleeping medication, such that neither group were heavily prescribed. Exercise improved sleep quality for poor sleepers, but the intensity mattered. Specifically, MICT and STRETCH improved sleep efficiency for poor sleepers, whereas HIIT did not (p < .05). The results suggest that both MICT and STRETCH may be more effective than HIIT for optimizing sleep in poor sleepers. These findings help to inform exercise guidelines for enhancing sleep in the aging population.